Penobscot materials, ACLS collection - Attean, Mitchell; Sapir, Edward, 1884-1939; Swadesh, Morris, 1909-1967 (1933)
The Penobscot materials in the ACLS collection consist of a single item in the "Malecite" section of the finding aid. Sapir and Swadesh's "Notes on Penobscot and Malecite" primarily consists of Penobscot, with additional Maliseet vocabulary. It contains a Penobscot alphabet, text, and carbon copy of texts from records with interlinear translations, and lexical items on slips. Recorded in part with speaker Mitchell Attean.